AB0561 AUTOMATIC QUANTIFICATION OF INTERSTITIAL LUNG DISEASE FROM CHEST COMPUTED TOMOGRAPHY IN SYSTEMIC SCLERODERMA. (2nd June 2020) - Carvalho, A.; Guimarães, A.; Sztajnbok, F. R.; Rodrigues, R.; Silva, B.; Lopes, A.; Almeida, I.; França, M.
Abstract : Background: Scleroderma-associated interstitial lung disease (SSc-ILD) is often observed in patients with systemic scleroderma (SSc) and its diagnosis contributes to early treatment decisions 1, 2 . Objectives: The present study aims to automatically quantify SSc-ILD from high-resolution chest-computed tomography (HRCT) and to evaluate the association between interstitial lung disease (ILD) extension and lung function impairment. Methods: Ninety-four patients with SSc and 27 lung-healthy subjects matched for gender, weight, height, and age underwent HRCT, spirometry and carbon monoxide diffusion capacity (DLCO ). SSc-ILD was determined as the tissue mass present between -500 and +100 Hounsfield Units normalized by the total lung tissue mass (TLM). Cut off was the highest value obtained in the control group (25% of TLM). All data are presented as mean and standard deviations (Table I). An ANOVA test followed by Bonferroni post-hoc correction was used for comparisons among groups. Results: From 94 patients with SSc, 64 were classified as having pulmonary involvement (SSc-ILD) and 30 as not having pulmonary involvement (SSc No-ILD). In SSc-ILD subjects, there was a significant reduction in forced vital capacity (FVC), carbon monoxide diffusion capacity (DLCO ) and carbon monoxide diffusion capacity normalized by alveolar ventilation (DLCO /A) when compared with SSc No-ILD and control group. Conclusion: The proposed method allows the automatic quantification of SSc-ILD from HRCT and ILD extent is associated with pulmonary function impairment. References: [1]Doyle TJ, Dellaripa PF. Lung Manifestations in the Rheumatic Diseases. CHEST. 2017 Dec;152(6):1283–95. [2]Saketkoo LA, Magnus JH, Doyle MK. The primary care physician in the early diagnosis of systemic sclerosis: the cornerstone of recognition and hope. The American Journal of the Medical Sciences. 2014 Jan;347(1):54–63. Disclosure of Interests: None declared